Analysis of Madelung disease based on sc-RNA sequencing: A case report and literature review. (May 2023) - Ma, Xiao; Ma, Shanshan; Cai, Dechao; Wang, Changming; Yu, Haoran; Xie, Juan; Cheng, Wendan
Abstract: Madelung disease (MD) was first described by Brodie in 1846 as a rare multiple lipoma. It is a benign tumor characterized by symmetrical diffuse adipose tissue deposition in the proximal extremities and neck. Until now, the etiology and pathogenesis of the disease have not been fully explained, resulting in difficulties in diagnosis and treatment; moreover, palliative treatment, such as surgical resection of adipose tissue or liposuction, is still the mainstream treatment for MD. However, the effectiveness of palliative surgery is limited, and most patients still relapse or metastasize after treatment. Therefore, we analyzed the relationship between tumor cells and immune cells in MD using single-cell RNA sequencing for the first time and combined an analysis of our results with a review of previous literature reports. Our study provides a new perspective on the pathogenesis of MD and provides a vital clinical basis for targeted therapy. Data Availability: The authors declare that all the data supporting the findings of this study are available within the article and its Supplemental information files. Highlights: Madelung disease (MD) is a rare metabolic disease whose etiology has not been fully elucidated. It is a benign tumor characterized by symmetrical diffuse adipose tissue deposition in the proximal extremities and neck. The diagnosis is mainly based on physical and histological examination, clinical features, and imaging. We reported on MD by using single-cell RNA sequencing for the first time and offered a new perspective on its biological characteristics, which is expected to provide a vital clinical basis for targeted therapy.